Learning Science for Pre-School and Elementary School Pupils Through Mini-Science Practicum at Rumah Pintar Mingguan Kreatif Ampang, Kuranji District, Padang - fatridha yansen (Fakultas MIPA Universitas Negeri Padang, 2025)
This activity aims to improve the ability and to increase the interest of children coming from low-income families at Rumah Pintar Mingguan Kreatif Ampang (RPM Ampang) to learn science through mini-science experiments. This practicum consists of two topics; the phenomenon of an erupting volcano and the inflation of a balloon without being blown up. This activity was attended by 31 pupils, and 5 RPM volunteers. The result of this community service activity is an increase in children's interest and motivation in the field of science, as well as an understanding of a topic through direct practicum using simple tools and materials to make learning more meaningful. In addition, RPM will make this mini science practicum activity a monthly routine activity in the RPM community with assistance from Universitas Sumatera Barat’s team to mentor their volunteers so that RPM can independently perform science experiments in the future. Keywords — Science experiment, Rumah Pintar, pre-school children, education disparity, chemistry